Efektivitas Sediaan Salep Limbah Kulit Singkong Sebagai Penyembuh Luka - Widia Nila Risnadewi; Nadya Arianita Turisia; Alsifah Nurhidayati; Candra Dwipayana Hamdin (LPPM Universitas Mataram, 2019)
The skin is an important organ that functions to receive stimuli such as touch, pain and other influences from the outside. Some problems that occur on the skin can becaused because the skin is very vulnerable to trauma and injury. Wound is a condition of the breakdown of tissue integrity caused by violence both mechanical, physical and chemical in nature. In general, wound care in the community is done with a dressing accompanied by compresses betadine and normal saline because these materials are easily available. However, long-term use of the dressing can cause slow wound healing and various infections can appear. This causes people to look for other alternative treatments, one of them with herbal plants, namely cassava plants have the potential to be used as a wound healing and is able to inhibit bacteria because they are suspected to contain phenolic compounds. This study was a true experimental study, the group of test animals was divided into 6 groups, after that the making of wounds and smeared with bacteria were given ointments with 3 concentrations namely 5%, 10%, and 15%. Ointment extract of cassava skin waste gives effect to the wound healing process seen from the length of the wound. The ethanol extract ointment which has a good effect on wound healing is an ointment with a concentration of 10% and 15%.